Inhibitory effect and related mechanism of decitabine combined with gemcitabine on proliferation of NK/T cell lymphoma cells - Lin, Lanke; Liu, Xiangqin; Yu, Hui; Deng, Huan; Peng, Kun; Chen, Jiang; Zhang, Chunle; Jiang, Tao; Liu, Xiaoqi (Frontiers in Pharmacology, 2023)
Background: EBV-associated lymphoma is a neoplasm with a poor prognosis, highly aggressive, and progressive rapidly. There is no standard clinical treatment protocol. Decitabine and gemcitabine are known to have anticancer properties against cells of various cancer, respectively. However, the effect of the combination medication on NK/T cell lymphoma cells and potential mechanisms have not been thoroughly investigated. Methods: Human NK/T cell lymphoma cells NK92MI were treated with decitabine and gemcitabine alone or in combination. Experiments, including the Cell Counting Kit-8 and flow cytometry, were performed to investigate how the combination of decitabine and gemcitabine affects the biological behavior of NK92MI cells in vitro. mRNA sequencing, RT-PCR, and western blotting were used to detect changes in the related signal pathway, mRNA, and protein expressions. Results: Decitabine and gemcitabine significantly inhibited the viability and proliferation of NK92MI cells in a dose-dependent manner. The combination index was less than 1 after treating with two drugs, which was a significant synergistic effect. The decitabine concentration with the best synergistic effect was 4.046 µM, and the gemcitabine concentration was 0.005 µM. Flow cytometry showed that combining two drugs could significantly promote apoptosis and arrest the cell cycle at the S phase. In the combined DAC and GEM group, caspase3 protein levels were higher than in either group alone or the control group. The transcriptome sequence, KEGG, and PPI analysis showed that the differential genes after combined treatment were mainly enriched in signal pathways related to cell proliferation, adhesion, and migration compared with using alone and control groups. Based on the sequencing results, we further investigated the role of DAC and GEM in ferroptosis-related signaling molecules using RT-PCR and Western blot techniques. RT-PCR and western blotting showed that the expression levels of HMOX1 and EBV cleavage gene BRLF1 were higher in the group with combined DAC and GEM than in the group alone and the control group, while the protein and mRNA expression levels of SLC7A11 were lower than the others. In addition, the GPX4 protein expression level in the combination group was lower than in the drug-alone and control groups. In addition, the combination treatment increased the ROS level of NK92MI cells. Conclusion: Our current findings suggested that decitabine had an inhibitory effect on the proliferation of NK92MI cells when co-treated with gemcitabine. This combination may increase the expression of ferroptosis-related signaling molecules, thus inhibiting the proliferation of NK92MI cells. It also promoted apoptosis in NK/T cell lymphoma. For patients with NK/T cell lymphoma, this novel combination may provide clinical benefits.